Experimental manipulation of dietary arsenic levels in great tit nestlings: Accumulation pattern and effects on growth, survival and plasma biochemistry. (February 2018) - Sánchez-Virosta, Pablo; Espín, Silvia; Ruiz, Sandra; Salminen, Juha-Pekka; García-Fernández, Antonio J.; Eeva, Tapio
Abstract: Arsenic (As) is a ubiquitous metalloid classified as one of the most hazardous substances, but information about its exposure and effects in free-living passerines is lacking. The aim of this study is to elucidate the effect of an As manipulation experiment on survival, growth and physiology of great tits ( Parus major ). Wild P. major nestlings inhabiting an unpolluted area were dosed with water, 0.2 or 1 μg g −1 d −1 of sodium arsenite (Control, Low and High As groups), whereas those living in a metal-polluted area were dosed with water (Smelter group). Birds accumulated As in tissues (liver, bone and feathers) in a dose-dependent way. Nestlings exposed to 1 μg g −1 d −1 of sodium arsenite showed reduced number of fledglings per successful nest, and those exposed to 0.2 μg g −1 d −1 had reduced wing growth, which could have post-fledging consequences such as increased predation risk. These results suggest that the LOAEL for effects on nestling survival and development in great tits is likely equal to or below 1 μg g −1 d −1 . However, limited effects on the biochemical parameters evaluated were found. It has been shown that As may produce oxidative stress and tissue damage, so further research exploring this issue will be carried out in a future study. Graphical abstract: Image 1 Highlights: We evaluate the effects of As on growth, survival and biochemistry in wild great tits. Birds accumulated As in liver, bone and feathers in a dose-dependent way. Nestlings exposed to 1 μg g −1 d −1 of sodium arsenite showed reduced number of fledglings. Nestlings exposed to 0.2 μg g −1 d −1 of sodium arsenite had reduced wing growth. Abstract : Biochemistry, growth and survival of wild Parus major nestlings dosed with arsenic.